Identification of early and extra-early maturing tropical maize inbred lines resistant to Exserohilum turcicum in sub-Saharan Africa - Badu-Apraku, Baffour; Bankole, F.A.; Ajayo, B.S.; Fakorede, M.A.B.; Akinwale, R.O.; Talabi, A.O.; Bandyopadhyay, Ranajit; Ortega Beltran, A. (Elsevier, 2021)
Northern corn leaf blight (NCLB) incited by the fungus Exserohilum turcicum is a foliar disease that significantly limits maize production and productivity in West and Central Africa (WCA), particularly in the mid-altitudes but during the last decade it has become a menace in lowland agro-ecologies. The most economical and environmentally friendly disease management strategy is the cultivation of maize varieties resistant or tolerant to NCLB. However, no early maturing (EM) and extra-early maturing (EEM) NCLB resistant varieties are commercially available in WCA. One hundred inbred lines each of EM and EEM derived from tropical maize germplasm were inoculated with a virulent isolate of E. turcicum at five locations in Nigeria during the 2017 and 2018 growing seasons. The objective of the study was to identify promising NCLB resistant lines and to investigate inter-relationships among the traits. Analysis of variance revealed highly significant genotype and genotype by environment (G × E) interactions for disease severity, grain yield (GYLD), and other agronomic traits. The average disease severity (TURC) values ranged from 1.9 to 5.8 and 2.9 to 5.7 for the EM and EEM inbred lines, respectively. The levels of reaction of the inbred lines to NCLB ranged from highly resistant to highly susceptible. Stepwise regression analysis showed that ears per plant, ear and plant aspects were significantly influenced by the disease scores. Ears per plant, ear and plant aspects, TURC and GYLD traits were employed to develop a base index (BI) for selecting NCLB resistant inbred lines for hybrid development. TZEI 135 and TZEEI 1 were outstanding in GYLD and also had the highest positive BI values in the EM and EEM inbred lines, respectively. The identification of NCLB resistant lines in this study has set the premise for development of NCLB resistant hybrids for WCA as well as the improvement of tropical maize breeding populations for NCLB resistance.